2006
DOI: 10.4049/jimmunol.176.12.7471
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-Neutralizing Monoclonal Antibody 4E10 Recognizes N-Terminal Sequences on the Native Antigen

Abstract: Characterization of the epitope recognized by the broadly neutralizing anti-HIV Ab 4E10 has, heretofore, focused on a linear sequence from the gp41 pretransmembrane region (PTMR). Attempts to generate neutralizing Abs based on this linear epitope sequence have been unsuccessful. We have characterized the antigenic determinants on recombinant glycosylated full-length Ags, and nonglycosylated and truncated Ags recognized by 4E10 using epitope extraction and excision assays in conjunction with MALDI mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
0
23
2
Order By: Relevance
“…Later, Zwick et al showed the 4E10 epitope comprises the linear sequence NWFDIT (aa 671 to 676), which is just C terminal to the 2F5 epitope in the MPER (273). As with 2F5, there is also conflicting information regarding the "full" 4E10 epitope, as a recent study suggested that 4E10 binds both FP at the N terminus of gp41 and the MPER epitope (95). Those authors hypothesized that the full 4E10 epitope was missing in previously reported studies because soluble gp41 does not include the FP.…”
Section: Mab 4e10 and Its Epitopementioning
confidence: 99%
“…Later, Zwick et al showed the 4E10 epitope comprises the linear sequence NWFDIT (aa 671 to 676), which is just C terminal to the 2F5 epitope in the MPER (273). As with 2F5, there is also conflicting information regarding the "full" 4E10 epitope, as a recent study suggested that 4E10 binds both FP at the N terminus of gp41 and the MPER epitope (95). Those authors hypothesized that the full 4E10 epitope was missing in previously reported studies because soluble gp41 does not include the FP.…”
Section: Mab 4e10 and Its Epitopementioning
confidence: 99%
“…Several human monoclonal Abs that neutralize a broad spectrum of HIV-1 variants have attracted considerable interest for vaccine design. Epitopes for these monoclonal Abs include the receptor binding domain of gp120 in the case of b12 (71,86), a glycan-specific epitope on gp120 in the case of 2G12 (13,85,86), and two adjacent epitopes in the membrane-proximal external region (MPER) of g41 in the cases of 2F5 and 4E10 (3,11,38,93). At least three of these monoclonal Abs have been shown to interact with FcRs and to mediate ADCC (42,43).…”
mentioning
confidence: 99%
“…[41][42][43][44][45] In addition we had shown that the binding of 2F5 is enhanced when in addition to the peptide containing its epitope a peptide corresponding to the FPPR is present, suggesting that the interaction between both peptides induces a conformation allowing a better binding of 2F5. 46 Whether this conformation is also required to induce broadly neutralizing antibodies remains unclear.…”
Section: Immunisation With Hybrid Proteinsmentioning
confidence: 91%